Sistem Informasi Registrasi Pelanggan FTTH pada PT Julia Multimedia Nusantara Menggunakan Metode Haversine: Sistem Informasi Registrasi Pelanggan FFTH pada PT. Julia Multimedia Nusantara Menggunakan Metode Haversine - Reza Maulana; Erfina Hisan; Haerul Azwar Herul (Jurnal INSYPRO (Information System and Processing), 2022)
PT Julia Multimedia Nusantara is one of the companies engaged in information and telecommunications which is located at Jalan Mapala Raya, Makassar, South Sulawesi. The services provided by PT JMN are ISP (Internet Service Provider) network infrastructure services, cable television services, CCTV installation services and smart home systems. Then over time PT JMN was able to expand its business by building a separate ISP (Internet Service Provider) network, which was named Julia-Net. Julia-Net has several services, one of which is the FTTH (Fiber to the home) service which is the latest service in the company. FTTH is a fiber optic network where the conversion point is at the customer's house. The problems faced by PT JMN are whether to register new customers and find the coordinates of the ODP (Optical Distribution Point) location. Employees are still doing manual processes starting from recording customers and finding ODP (Optical Distribution Point) location points with direct surveys to the field. Keywords: FTTH customer registration information system